Knowledge Transfers from Multinational to Domestic Firms: Evidence from Worker Mobility – A Replication-Robustness Study of Poole (2013) - Stefanie A. Haller; Eoin T. Flaherty; Ragnhild Balsvik; Stefanie Haller (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper replicates Poole (2013) using comprehensive Norwegian and Irish register data. Our results largely confirm the evidence documented in Poole for Brazil which suggests that when workers leave multinationals and are rehired at domestic establishments, the wages of their new coworkers who have already been present in the plant increase. However, unlike suggested in the original article there is little indication that these spillovers differ in a statistically significant way across various dimensions of heterogeneity for any of the three countries.
Keywords: F23; F61; J31; 330; multinational firms; wage spillovers; worker mobility; replication